Inflation, taxation, capital-markets and the demand for housing in Ireland - Irvine, Ian (Economic & Social Studies, 1986)
The objective of this paper is to examine the effect of inflation on the quantity of housing demanded where mortgage interest payments are tax deductable and where capital markets set a limit upon the amount which can be borrowed to purchase a house. It is illustrated theoretically that the answer to this question depends upon the potential housebuyer's marginal tax rate. A micro simulation model is then constructed to examine the likely numerical effects on demand of different rates of inflation. The results indicate that demand, on the part of a typical potential buyer, should increase in response to a lowering of the inflation rate. The simulation model also indicates that the real value of lax savings increase in response to a lower inflation rate. These conclusions differ substantially from what would be obtained in other economies whose tax laws are similar in intent. The difference is attributable to the ceiling on tax deductible interest payments in Ireland. A subsidiary objective of the paper is to examine the tax cost of current government measures designed to encourage house purchase. It is illustrated that the tax rate at which households may deduct interest payments could be reduced with only a minor effect on housing demand.
Keywords: Taxation - Ireland; Property market - Ireland